2023
DOI: 10.2147/jaa.s405297
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Diagnostic Coding for Asthma in an Electronic Health Record System in Hong Kong

Abstract: Background: Electronic health record (EHR) databases can facilitate epidemiology research into various diseases including asthma. Given the diagnostic challenges of asthma, the validity of the coding in EHR requires clarification. We aimed to assess the validity of International Classification of Diseases, 9th Revision (ICD-9) code algorithms for identifying asthma in the territory-wide electronic medical health record system of the Clinical Data Analysis and Reporting System (CDARS) in Hong Kong. Methods: Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The database has been widely used in depression-related epidemiological studies 13 , 15 , 19 with reliable and validated diagnostic codes. 24 , 25 In this study, we identified a cohort of patients aged above 10 years with newly diagnosed depression (ICD-9-CM: 296.2, 300.4, 311) between 2014 and 2016 from the database (the “2014–2016 cohorts” thereafter). New diagnosis was ascertained by reviewing diagnosis records since 1993, when the database was first available.…”
Section: Methodsmentioning
confidence: 99%
“…The database has been widely used in depression-related epidemiological studies 13 , 15 , 19 with reliable and validated diagnostic codes. 24 , 25 In this study, we identified a cohort of patients aged above 10 years with newly diagnosed depression (ICD-9-CM: 296.2, 300.4, 311) between 2014 and 2016 from the database (the “2014–2016 cohorts” thereafter). New diagnosis was ascertained by reviewing diagnosis records since 1993, when the database was first available.…”
Section: Methodsmentioning
confidence: 99%
“…We traced patients' records back to 3 years before the index date. Demographics including age at index date, sex; lifestyle factors including alcohol consumption and smoking; The comorbidities were defined based on the combination of ICD9/ICD10 codes which had been previously validated 24 , 25 , 26 and medications prescribed, including hypertension, diabetes, obesity, stroke, anaemia, coronary artery disease (CAD), peripheral vascular disease (PVD), dyslipidaemia, atrial fibrillation (AF), other arrhythmias, cirrhosis, chronic renal failure (CRF), hearing loss, head injury, cancer, Parkinson's disease, rheumatism, depression, sleep apnea; Medications including antiplatelets, angiotensin-converting enzyme inhibitors (ACEI), angiotensin receptor blocker (ARB), beta-blockers, calcium channel blockers (CCB), diuretics, statins, insulin, and other anti-diabetics; Education status (SES) including less than primary, primary, secondary, tertiary and higher education were retrieved from CDARS. Baseline drug use was defined as ≥90 days of consecutive drug use within 3 years before the index date.…”
Section: Methodsmentioning
confidence: 99%
“…24 Patients with underlying COPD, asthma, bronchiectasis and ILD were identified using the following ICD-9 diagnostic codes of 493.x, 496.x, 494.x and 516.3/517.2/517.8/714.81/495, respectively. [25][26][27] Patients who had a previous history of COVID-19, who received MOL or NMV-r in an outpatient setting before hospitalization, who received remdesivir treatment, received both MOL and NMV-r in the same index admission (simultaneous or sequential) and those requiring supplementary oxygen upon admission were excluded. The cohort was followed-up until 30th June 2023.…”
Section: Methodsmentioning
confidence: 99%